Epidemiology of patients with breast cancer assisted in a hospital unit in Maceió-AL submitted to neoadjuvant chemotherapy (Research, Society and Development, 2022)
Introduction: Breast cancer is the second leading cause of disease and death in the world, with a wide variation in incidence and mortality between countries due to socioeconomic status and exposure to risk factors related to social conditions and lifestyle. The objective of this work is to trace the profile of women with breast cancer treated in an oncology unit in Maceió (Alagoas) undergoing neoadjuvant chemotherapy. Methodology: Cross-sectional analytical observational study with data collection from medical records of patients diagnosed with breast cancer assisted in a cancer hospital unit in Maceió-AL for the years 2019 and 2020. Results: It was found that there is a predominance of diagnosis of breast cancer treated with neoadjuvant chemotherapy at ages between 50 and 70 years and that comorbidities had a high correlation with this neoplasm, with 60% of the participants being obese, 29.09% smokers and 21.81% alcoholics. Neoadjuvant therapy was performed with the doxorubicin, cyclophosphamide and paclitaxel therapy in 96.36% of the participants, of which 56.36% had a complete pathological response. Conclusion: Maintaining healthy lifestyle habits and periodic screening for the early diagnosis of breast cancer are essential for a good prognosis of this disease, allowing greater chances of a complete pathological response after treatment.